Sports tourism as economic development boosters / Dr Wan Normila Mohamad - Mohamad, Wan Normila (Universiti Teknologi MARA, Negeri Sembilan, 2023)
Globally, sports tourism is indeed recognized as a growing segment within the tourism industry with substantial economic potential. Sports tourism refers to the travel and participation in sporting events, competitions, or activities with people traveling to different destinations to watch or participate in sports-related events, tournaments, matches and other activities. The World Tourism Organisation projects that international tourist arrivals could reach 80% to 95% of pre-pandemic levels in 2023 (versus 63% in 2022) despite lingering global headwinds (The Star, 2023). According to a report by UOB Global Economics and Markets Research, the expected stronger tourism activity further supports its economic growth forecast of 4% for Malaysia in 2023 (The Star, 2023). Based on the revised Malaysian Budget 2023, tabled by the Prime Minister, Datuk Seri Anwar Ibrahim, there is a substantial increase in the allocation for the Youth and Sports Ministry. In fact, the government has allocated RM399 million to the ministry, which marks a significant increase compared to the RM289 million allocation in 2022.